A mouse organotypic tissue culture model for autosomal recessive congenital ichthyosis. (13th November 2014) - Rosenberger, S.; Dick, A.; Latzko, S.; Hausser, I.; Stark, H.‐J.; Rauh, M.; Schneider, H.; Krieg, P.
Summary Background Autosomal recessive congenital ichthyoses (ARCIs) are keratinization disorders caused by impaired skin barrier function. Mutations in the genes encoding the lipoxygenases 12R‐LOX and eLOX‐3 are the second most common cause of ARCIs. In recent years, human skin equivalents recapitulating the ARCI phenotype have been established. Objectives To develop a murine organotypic tissue culture model for ARCI. Methods Epidermal keratinocytes were isolated from newborn 12R‐LOX‐deficient mice and cocultivated with mouse dermal fibroblasts embedded in a scaffold of native collagen type I. Results With this experimental set‐up the keratinocytes formed a well‐organized multilayered stratified epithelium resembling skin architecture in vivo. All epidermal layers were present and the keratinocytes within showed the characteristic morphological features. Markers for differentiation and maturation indicated regular epidermal morphogenesis. The major components of epidermal structures were expressed, and were obviously processed and assembled properly. In contrast to their wild‐type counterparts, 12R‐LOX‐deficient skin equivalents showed abnormal vesicular structures in the upper epidermal layers correlating with altered lipid composition and increased transepidermal water loss, comparable with 12R‐LOX‐deficient mice. Conclusions The mouse skin equivalents faithfully recapitulate the 12R‐LOX‐deficient phenotype observed in vivo, classifying them as appropriate in vitro models to study molecular mechanisms involved in the development of ARCI and to evaluate novel therapeutic agents. In contrast to existing human three‐dimensional skin models, the generation of these murine models is not constrained by a limited supply of material and does not depend on in vitro expansion and/or genetic manipulations that could result in inadvertent genotypic and phenotypic alterations.